Derivation of oxygen-containing functional groups on biochar under non-oxygen plasma for mercury removal. (1st September 2020) - Zhang, Huicong; Wang, Tao; Chen, Wei-Yin; Zhang, Yongsheng; Sun, Baomin; Pan, Wei-Ping
Graphical abstract: Highlights: Biochar adsorbed oxygen and water from the air during storage. Adsorbed O2 dominates the generation of oxygen-containing functional group in plasma. O–CO is only generated on H2 O adsorbed biochar under non-oxygen plasma. The generated oxygen-containing functional group oxidises Hg 0 to HgO. Abstract: Biochar was subjected to N2 -plasma treatment after adsorbing water or oxygen. The mercury removal efficiency of the obtained samples was tested. The results of H2 O-thermogravimetric and O2 -temperature programmed desorption show that biochar had adsorption capacity for both water and oxygen during storage. The adsorbed water exhibited an inhibitory effect on mercury removal. However, after plasma treatment, water decomposed into oxygen-containing active radicals and combined with biochar to form oxygen-containing functional groups. The generated functional groups compensated for the inhibition of mercury capture. After the biochar adsorbed oxygen, the biochar was easily sintered under plasma, thereby reducing the mercury removal performance. The oxygen-containing functional groups formed by plasma treatment of oxygen adsorbed biochar also improved the mercury removal efficiency. Hg-temperature programmed desorption revealed that Hg 0 could be oxidised by the generated oxygen-containing functional group to form HgO. Correlation analysis showed that the oxygen adsorbed by the biochar from air during storage was the main source of oxygen-containing functional groups generated under a non-oxygen plasma environment. The correlation coefficient was up to 0.999. During normal storage, the oxygen adsorbed by the adsorbent from the air can be converted into oxygen-containing functional groups during the plasma modification process, thereby oxidising Hg 0 .